Successful credit control - Posner, Martin (Chichester ; New York : John Wiley and Sons, 1998)
This book is about: The basic principles of credit assessment; Creating profitable sales and customer care; Types of business; The unknown customer; Making the assessment; Training for credit management; collecting the outstanding account; Thinking about taking proceedings; ...
Keywords: Management; Credit; Credit -- Management; Export credit -- Great Britain